A Pueblo Social History : Kinship, Sodality, and Community in the Northern Southwest - Ware, John A. (John Allen) (Book collections on Project MUSE., 2014)
"In A Pueblo Social History, John Ware challenges modern anthropologists to break down the walls between archaeology and ethnography in order to obtain a more complete understanding of Pueblo prehistory in the American Southwest."--publisher.